MOTIVASI MOTIVASI PENDAKI PADA KEGIATAN OLAHRAGA REKREASI MOUNTAIN HIKING DI GUNUNG TALANG - M. Alvin Wijaya, M. Alvin Wijaya; Alimuddin; Anton Komaini; Fahmil Haris (Jurnal IKEOR, 2024)
Abstract The aim of this research is to determine the motivation of climbers in mountain hiking recreational sports activities on Mount Talang Aie Batumbuak, Gunung Talang District, Solok Regency. The population in this study was sampled using the Incidental Sampling Technique. According to (Sugiyono, 2016:124) Incidental Sampling is anyone who coincidentally/incidentally meets the researcher can be used as a sample, if it is deemed that the person they happen to meet is suitable as a data source. So, the sample in this study was 50 climbers in mountain hiking recreational sports activities with an age range of 15-35 years. The test instrument used in this research uses a closed questionnaire and the scale used is the sensation seeking scale compiled by (in Anita Faulana, 2020) which has been tested for validity and reliability. The data analysis technique in this research uses descriptive statistical formulas, namely searching for values ​​by searching for percentages The results of this research obtained a maximum score of 200 with an average of 3.68 and a standard deviation of 0.30 with an average of the highest score of 4.02 and the lowest score of 3.35. So it can be concluded that the motivation of climbers in recreational sports activities mountain hiking Talang because he likes the challenge of the activity itself, which stimulates adrenaline or arouses passion like being involved in a challenging activity. Keywords: Motivation, Mountain Climber, Mountain Hiking.